Evaluating the RIST Molecular-Targeted Regimen in a Three-Dimensional Neuroblastoma Spheroid Cell Culture Model - Kaess, Carina; Matthes, Marie; Gross, Jonas; Waetzig, Rebecca; Heise, Tilman; Corbacioglu, Selim; Sommer, Gunhild (Cancers, 2023)
Background: The outcome for patients with high-risk neuroblastoma remains poor and novel treatment strategies are urgently needed. The RIST protocol represents a novel metronomic and multimodal treatment strategy for high-risk neuroblastoma combining molecular-targeted drugs as ‘pre-treatment’ with a conventional chemotherapy backbone, currently evaluated in a phase II clinical trial. For preclinical drug testing, cancer cell growth as spheroid compared to mo-nolayer cultures is of advantage since it reproduces a wide range of tumor characteristics, including the three-dimensional architecture and cancer stem cell (CSC) properties. The objective of this study was to establish a neuroblastoma spheroid model for the rigorous assessment of the RIST treatment protocol. Methods: Evaluation of CSC marker expression was performed by mRNA and protein analysis and spheroid viability by luminescence-based assays. Aberrant expression of RNA-binding protein La in neuroblastoma was assessed by tissue microarray analysis and patients’ data mining. Results: Spheroid cultures showed increased expression of a subgroup of CSC-like markers (CXCR4, NANOG and BMI) and higher Thr389 phosphorylation of the neuroblastoma-associated RNA-binding protein La when compared to monolayer cultures. Molecular-targeted ‘pre-treatment’ of spheroids decreased neoplastic signaling and CSC marker expression. Conclusions: The RIST treatment protocol efficiently reduced the viability of neuroblastoma spheroids characterized by advanced CSC properties.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3D model; cancer stem cells; CSC; La (LARP3; La autoantigen); La/SSB; neuroblastoma; RIST; RNA-binding protein; spheroids; three-dimensional